From Ru’yah al-Hilal to Maliek Bulan: The Determination of Ramadan in The Tarekat Syattariyah (TS) - Ziaulhaq Hidayat (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This article presents ru’yah al-hilal as a marker for implementing Ramadan fasting among the Tarekat Syattariyah (TS). Ru’yah al-hilal is important for TS because it is one of the doctrines that must be implemented. The ru’yah al-hilal doctrine inspired the birth of the maliek bulan tradition, which is carried out openly every year by TS adherents and the general public. To understand the ru’yah al-hilal doctrine in TS, a research question is asked how the ru’yah al-hilal doctrine can become a maliek bulan tradition among TS. This study found that the doctrine of ru’yah al-hilal originates from the al-Qur’an and hadith, which speak of ru’yah al-hilal as the precursor of the beginning of Ramadan. However, this normative doctrine is still general. To understand the doctrine of ru’yah al-hilal, the TS group interprets it through the maliek bulan tradition, which is carried out every year to ensure the fasting time of Ramadan. The results of the maliek bulan will be conveyed to all TS networks in various regions in Indonesia to serve as a guideline for the start of the implementation of Ramadan fasting.